2010
DOI: 10.1088/1475-7516/2010/01/007
|View full text |Cite
|
Sign up to set email alerts
|

Minimum mass of galaxies from BEC or scalar field dark matter

Abstract: Many problems of cold dark matter models such as the cusp problem and the missing satellite problem can be alleviated, if galactic halo dark matter particles are ultralight scalar particles and in Bose-Einstein condensate (BEC), thanks to a characteristic length scale of the particles. We show that this finite length scale of the dark matter can also explain the recently observed common central mass of the Milky Way satellites (∼ 10 7 M ⊙ ) independent of their luminosity, if the mass of the dark matter partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 63 publications
5
84
0
1
Order By: Relevance
“…From this it follows that galaxies can share some properties because they formed in the same manner and at the same moment [67]. Therefore, from this paradigm we have to expect that there exists well formed galaxy halos at higher redshifts than in the ΛCDM model.…”
Section: Why Scalar Field Dark Matter?mentioning
confidence: 91%
See 2 more Smart Citations
“…From this it follows that galaxies can share some properties because they formed in the same manner and at the same moment [67]. Therefore, from this paradigm we have to expect that there exists well formed galaxy halos at higher redshifts than in the ΛCDM model.…”
Section: Why Scalar Field Dark Matter?mentioning
confidence: 91%
“…Robles and Matos [104], (see also [18,16,51]) showed that BEC dark matter halos fit very well high-resolution rotation curves of LSB galaxies, and that the constant density core in dark halos can be reproduced. Also, [67] showed how the SFDM/BEC paradigm is a good alternative to explain the common mass of the dark halos of dwarf spheroidal galaxies. Recently, Rindler-Daller and Shapiro, [103], investigated the formation of vortex in SFDM/BEC halos.…”
Section: Why Scalar Field Dark Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…which leads to the minimum length scale and the mass scale of galactic halos formed at z [62][63][64]. Dwarf galaxies are the smallest dark-matter-dominated objects and, hence, are ideal objects for understanding the nature of dark matter.…”
mentioning
confidence: 99%
“…The BEC predicts that the size of the galaxies increases as the Hubble radius of the universe even without merging, which agrees well with the recent observational data. In [20] it was shown that the finite length scale of the condensate dark matter can explain the recently observed common central mass of the Milky Way satellites (∼ 10 7 M ⊙ ) independent of their luminosity, if the mass of the dark matter particle is about 10 −22 eV.…”
Section: Introductionmentioning
confidence: 99%